Synthesis, Characterization and Study of In Vitro Antimicrobial Activity of Some Substituted N'-[Arylidene]-2-(5-Phenyl-1HTetrazol- 1-yl) Acetohydrazide: Synthesis and study of antimicrobial activity of substituted acetohydrazide - Popat B. Mohite,; Vaidhun H. Bhaskar, (Iranian Journal of Pharmaceutical Sciences, 2010)
Reaction of 5-phenyl tetrazole with ethyl chloroacetate to form ethyl (5-phenyl-1H-tetrazol-1-yl) acetate (1). Compound 1 react with hydrazine hydrate in ethanol yield 2-(5-phenyl-1H-tetrazol-1-yl) acetohydrazide (2). The condensation of (2) with various aldehydes yield the corresponding substituted N'-[-arylidene]-2-(5-phenyl-1H-tetrazol-1-yl) acetohydrazide (3a- j). The compounds obtained were identified by spectral data and have been screened for antimicrobial activity. The most promising compounds having good antibacterial activity were 3b, 3c and 3i, and the best for antifungal activity were 3b, 3c and 3e.